Extraction of β-glucan from Saccharomyces cerevisiae: Comparison of different extraction methods and in Vivo assessment of immunomodulatory effect in mice - Pengkumsri N. (2017)
© 2017, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved. Beta-glucan (BG) is a conserved cell wall components of bacteria, fungi, and yeast. BG is an immunomodulator and stimulates the host immune system. This study was performed to screen Saccharomyces cerevisiae strain with high BG, extraction of BG using different chemical extraction methods, composition analysis of BG, and evaluation of the immunomodulatory effect of high-quality BG using mice model. Ten yeast strains were screened for high BG content using total glucan extraction kit and were subjected to FT-IR analysis. The kit based extraction revealed that HII31 showed a high content of total glucan and BG. HII31 cells were subjected to four different acid/base extractions, which indicated that combination of a strong base (NaOH) and weak acid (CH 3 COOOOH) extraction recovered high BG and a high ratio of polysaccharide, protein, and lipid. Further, the immunomodulatory effect of the selected BG was evaluated using mice, which suggested that low dose of HII31-BG induces the expression of selected pro-inflammatory (IL-17, IFN-γ) and anti-inflammatory cytokine (IL-10) significantly, whereas relatively high dose was required to alter the IL-6 and TGF-β expression. Overall, the present study revealed that BG extracted from HII31 cells alters the expression of studied cytokines, which can be used as a potent immunomodulator in pharmaceutical products.